Alizarin glucosyl transferase activity in Streptomyces aureofaciens mutants - Matĕjů, J; Nohýnek, M (Folia microbiologica, 1991)
Alizarin glucosyl transferase activity was found in five mutant strains of Streptomyces aureofaciens. The activity bears no direct relationship to the final products of tetracycline biosynthesis.
Keywords: glukosyltransferasy; mutageneze; glukosidy; Streptomyces aureofaciens; Glucosides; Anthraquinones; anthrachinony; Mutagenesis; Glucosyltransferases